An efficacy trial of an electronic health record-based strategy to inform patients on safe medication use: The role of written and spoken communication. Issue 9 (September 2016) - Curtis, Laura M.; Mullen, Rebecca J.; Russell, Allison; Fata, Aimee; Bailey, Stacy C.; Makoul, Gregory; Wolf, Michael S.
Highlights: We leveraged an EHR to deliver education materials at the point of prescribing. Fidelity of the EHR strategy to deliver medication education materials was high. Physician counseling was high for indication and directions, but low for risks. Both 'MedSheets' and physician counseling impacted patient understanding of risks. The receipt of both written information and verbal counseling was most beneficial on patient understanding of risks. Abstract: Objective: We tested the feasibility and efficacy of an electronic health record (EHR) strategy that automated the delivery of print medication information at the time of prescribing. Methods: Patients (N = 141) receiving a new prescription at one internal medicine clinic were recruited into a 2-arm physician-randomized study. We leveraged an EHR platform to automatically deliver 1-page educational 'MedSheets' to patients after medical encounters. We also assessed if physicians counseled patients via patient self-report immediately following visits. Patients' understanding was objectively measured via phone interview. Results: 122 patients completed the trial. Most intervention patients (70%) reported receiving MedSheets. Patients reported physicians frequently counseled on indication and directions for use, but less often for risks. In multivariable analysis, written information (OR 2.78, 95% CI 1.10–7.04) and physician counseling (OR 2.95, 95% CI 1.26–6.91) were independently associated with patient understanding of risk information. Receiving both was most beneficial; 87% of those receiving counseling and MedSheets correctly recalled medication risks compared to 40% receiving neither. Conclusion: An EHR can be a reliable means to deliver tangible, print medication education to patients, but cannot replace the salience of physician-patient communication. Practice implications: Offering both written and spoken modalities produced a synergistic effect for informing patients.